Yawning in neurology: a review - Teive, Hélio A. G.; Munhoz, Renato P.; Camargo, Carlos Henrique F.; Walusinski, Olivier (Arquivos de Neuro-Psiquiatria, 2018)
Yawning is a stereotyped physiological behavior that can represent a sign or symptom of several conditions, such as stroke, parakinesia brachialis oscitans, parkinsonism, Parkinson’s disease and epilepsy. More rarely, it can occur in patients with intracranial hypertension, brain tumor, multiple sclerosis, migraine, Chiari malformation type I, and amyotrophic lateral sclerosis. Drug-induced yawning is an uncommon clinical condition and yawning in patients with autism or schizophrenia is very rare. The aim of this review is to describe in detail the occurrence of the phenomenon in such conditions, and its’ phenomenology and pathophysiology.
Keywords: yawning; parakinesia, stroke